A study on the establishment of Tunnel Contour Quality Index considering construction cost. (August 2015) - Kim, Yangkyun; Bruland, Amund
Graphical abstract: Highlights: Tunnel Contour Quality Index (TCI) has been previously suggested by the authors. TCIC is suggested to consider the effect of a contour quality on construction cost. Construction costs include blasting, muckpile, shotcrete, and concrete. TCIC includes unit construction costs, unit conversion coefficients and two parameters. Weights for the two parameters are a relative ratio of two operation groups. Abstract: Tunnel Contour Quality Index (TCI) has been proposed in previous studies to quantify a contour quality resulting from blasting in a tunnel or underground space, and to effectively compare the contour quality with other cases. TCI evaluates general geometric features of a tunnel contour with three parameters regarding overbreak, three weights, three correction factors and one range adjustment constant. This paper proposes another concept of TCI to consider the effect of a contour quality on construction cost. This index is termed TCIC (Tunnel Contour Quality Index for construction cost) to be distinguished from the existing TCI. TCIC consists of two parameters, two weights and one constant for range adjustment. The two parameters are defined by three elements, i.e., average depth of overbreak, the ratio of actual contour length to planned length, and longitudinal overbreak difference, representing increased tunnel volume and increased contour area for a given contour condition. This analysis can be made by simplifying the tunnel into a semi-circular truncated cone having the same three elements. The two weights are constants represented by the unit cost ratio between two operation groups, i.e., one group for blasting, muckpile and concrete lining costs, and the other group for shotcrete and waterproof membrane. To check the feasibility of the index, the contour quality of two tunnels (5 detailed tunnels) in Norway is evaluated by TCIC, based upon the unit construction costs for other two Norwegian tunnels. The result shows that the range of TCIC is between 34 and 55. It is thought that the difference % in TCIC is similar to the difference % in the unit construction cost increased due to the contour quality. In addition, a statistical analysis shows that a usual range of TCIC is between 30 and 61. Finally, it is thought that TCIC can be used as a tool not only to evaluate contour quality, but also to estimate the construction cost increased due to a contour quality in a tunnel project.